Spontaneous pneumothorax and pneumomediastinum associated with severe COVID-19 pneumonia. A case report - Azañero-Haro, Johan (2025)
During the COVID-19 pandemic, acute respiratory failure, often associated with acute respiratory distress syndrome, required a broad differential diagnosis that demanded several therapeutic interventions. We present the case of a 41-year-old with COVID-19 who presented pneumothorax and pneumomediastinum. The insertion of a chest tube immediately improved his respiratory distress. Follow-up images revealed the resolution of the pneumothorax and pneumomediastinum. This case emphasizes the potentially lethal complications of spontaneous pneumothorax and pneumomediastinum in COVID-19 patients.